Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $E$ be a vector bundle over $M$ and denote by $\mathcal{A}^k(E)$ the space of sections of $\Lambda^k (TM)^* \otimes E$, i.e. the space $k$-forms with values in $E$.

A connection $\nabla:\mathcal{A}^0(E) \to \mathcal{A}^1(E)$ extends to a map $\nabla:\mathcal{A}^k(E) \to \mathcal{A}^{k+1}(E)$ by setting $\nabla(\alpha \otimes s)= d \alpha \otimes s + (-1)^k \alpha \wedge\nabla s$ and we can define the curvature of $\nabla$ as the composition $F_\nabla=\nabla \circ \nabla: \mathcal{A}^0(E) \to \mathcal{A}^2(E)$.

From the Leibniz rule one can see that $F_{\nabla}(fs) = f F_{\nabla}(s)$ and therefore we can view $F_\nabla$ as an element of $\mathcal{A}^2(\text{End}(E))$ ($F_\nabla$ evaluated at a pair of tangent vectors is the endomorphism $s \mapsto F_\nabla(X,Y)(s)$.

My question is whether the formula $F_{\nabla}(X,Y) = \nabla_X \nabla_Y - \nabla_Y \nabla_Y - \nabla_{[X,Y]}$ holds true.

I could prove it when $E=TM$ and $\nabla$ is a torsion free connection (because in that case we have a formula relating the exterior derivative with $\nabla$) but I don't know how to deal with the general case.

share|improve this question

2 Answers 2

up vote 4 down vote accepted

Short answer: the formula is true. Long answer: see below for the calculation.

Choose local coordinates $(x^1, \ldots, x^n)$ and a local frame field $(e_1, \ldots, e_r)$ for $E$, both of these over an open neighbourhood $U$, and let $\newcommand{\Tud}[3]{{#1}^{#2}_{\phantom{#2}{#3}}}$ $$\nabla e_\mu = \Tud{\omega}{\nu}{\mu} \otimes e_\nu$$ for some $\Tud{\omega}{\nu}{\mu} \in \Omega^1(U)$. (I am using the summation convention for repeated indices.) Let $\Tud{\Omega}{\nu}{\mu} \in \Omega^2(U)$ be such that $$\nabla \nabla e_\mu = \Tud{\Omega}{\nu}{\mu} \otimes e_\nu$$ Now, by the Leibniz rule, we have $$\nabla \nabla e_\mu = \mathrm{d}\Tud{\omega}{\nu}{\mu} \otimes e_\nu - \Tud{\omega}{\nu}{\mu} \wedge \Tud{\omega}{\rho}{\nu} \otimes e_\rho$$ thus, $$\Tud{\Omega}{\nu}{\mu} = \mathrm{d}\Tud{\omega}{\nu}{\mu} + \Tud{\omega}{\nu}{\rho} \wedge \Tud{\omega}{\rho}{\mu}$$

Since $$\nabla (W^\mu e_\mu) = \mathrm{d} W^\mu \otimes e_\mu + W^\mu \Tud{\omega}{\nu}{\mu} \otimes e_\nu$$ we have $$\nabla \nabla (W^\mu e_\mu) = \mathrm{d} W^\mu \wedge \Tud{\omega}{\nu}{\mu} \otimes e_\nu + W^\mu \, \mathrm{d} \Tud{\omega}{\nu}{\mu} \otimes e_\nu - \mathrm{d}W^\mu \wedge \Tud{\omega}{\nu}{\mu} \otimes e_\nu - W^\mu \Tud{\omega}{\nu}{\mu} \wedge \Tud{\omega}{\rho}{\nu} \otimes e_\rho$$ thus, $\nabla \nabla$ is indeed $C^\infty(U)$-linear, with $$\nabla \nabla (W^\mu e_\mu) = W^\mu \Tud{\Omega}{\nu}{\mu} \otimes e_\nu = W^\mu \nabla \nabla e_\mu$$ This means we only need to check the formula for the frame field instead of arbitrary sections of $E$.

Now, observe that, if $X$ and $Y$ are vector fields, $$\begin{align} \nabla_X \nabla_Y e_\mu = \nabla_X ( \langle \Tud{\omega}{\nu}{\mu} , Y \rangle e_\nu) & = \langle \mathrm{d} \langle \Tud{\omega}{\nu}{\mu} , Y \rangle, X \rangle e_\nu + \langle \Tud{\omega}{\nu}{\mu} , Y \rangle \langle \Tud{\omega}{\rho}{\nu} , X \rangle e_\rho \\ \nabla_Y \nabla_X e_\mu = \nabla_Y ( \langle \Tud{\omega}{\nu}{\mu} , Y \rangle e_\nu) & = \langle \mathrm{d} \langle \Tud{\omega}{\nu}{\mu} , X \rangle, Y \rangle e_\nu + \langle \Tud{\omega}{\nu}{\mu} , X \rangle \langle \Tud{\omega}{\rho}{\nu} , Y \rangle e_\rho \\ \nabla_{[X, Y]} e_\mu & = \langle \Tud{\omega}{\nu}{\mu} , [X, Y] \rangle e_\nu \end{align}$$ where I have written $\langle - , - \rangle$ for the canonical pairing of a 1-form and a vector field. So we have $$\begin{align} (\nabla_X \nabla_Y - \nabla_Y \nabla_X - \nabla_{[X, Y]}) e_\mu & = (\langle \mathrm{d} \langle \Tud{\omega}{\nu}{\mu} , Y \rangle, X \rangle - \langle \mathrm{d} \langle \Tud{\omega}{\nu}{\mu} , X \rangle, Y \rangle - \langle \Tud{\omega}{\nu}{\mu} , [X, Y] \rangle) \, e_\nu \\ & \phantom{=} + (\langle \Tud{\omega}{\nu}{\rho} , X \rangle \langle \Tud{\omega}{\rho}{\mu} , Y \rangle - \langle \Tud{\omega}{\nu}{\rho} , Y \rangle \langle \Tud{\omega}{\rho}{\mu} , X \rangle) \, e_\nu \end{align}$$ while on the other hand $$\Tud{\Omega}{\nu}{\mu} (X, Y) = \langle \Tud{\Omega}{\nu}{\mu} , X \wedge Y \rangle = \langle \mathrm{d}\Tud{\omega}{\nu}{\mu} , X \wedge Y \rangle + \langle \Tud{\omega}{\nu}{\rho} \wedge \Tud{\omega}{\rho}{\mu} , X \wedge Y \rangle$$ but by Cartan's formula for the exterior derivative $$\langle \mathrm{d}\Tud{\omega}{\nu}{\mu} , X \wedge Y \rangle = \langle \mathrm{d} \langle \Tud{\omega}{\nu}{\mu} , Y \rangle , X \rangle - \langle \mathrm{d} \langle \Tud{\omega}{\nu}{\mu} , X \rangle , Y \rangle - \langle \Tud{\omega}{\nu}{\mu} , [X, Y] \rangle$$ Now, by definition $$\langle \Tud{\omega}{\nu}{\rho} \wedge \Tud{\omega}{\rho}{\mu} , X \wedge Y \rangle = \langle \Tud{\omega}{\nu}{\rho} , X \rangle \langle \Tud{\omega}{\rho}{\mu}, Y \rangle - \langle \Tud{\omega}{\nu}{\rho} , Y \rangle \langle \Tud{\omega}{\rho}{\mu}, X \rangle $$ and so $$\Tud{\Omega}{\nu}{\mu} (X, Y) e_\nu = (\nabla_X \nabla_Y - \nabla_Y \nabla_X - \nabla_{[X, Y]}) e_\mu $$ which is exactly what we want.

share|improve this answer

I guess I've found an alternative computation. Can anyone tell me if this is right?

Let $s\in \mathcal A^0(E)$ a section and consider $\nabla s \in \mathcal A^1(E)$. By linearity we may assume that $\nabla s = \alpha \otimes t$ with $\alpha$ a 1-form and therefore $\nabla_X s = \alpha(X)t$.

If $X,Y$ are vector fields, the invariant formula for the exterior derivative gives $d \alpha (X,Y)= X \alpha(Y) - Y\alpha(X) - \alpha([X,Y])$ and therefore

$F_\nabla(X,Y)(s) = \nabla(\alpha \otimes t)(X,Y) = (d \alpha \otimes t - \alpha \wedge \nabla t)(X,Y)$

$=(d \alpha)(X,Y)t - \alpha(X) \nabla_Y t + \alpha(Y) \nabla_X t$

$= [X \alpha(Y) - Y\alpha(X) - \alpha([X,Y])]t - \alpha(X) \nabla_Y t + \alpha(Y) \nabla_X t$

$= (X \alpha(Y))t + \alpha(Y)\nabla_X t - (Y \alpha(X))t - \alpha(X)\nabla_Y t - \alpha([X,Y])t $

$= \nabla_X (\alpha(Y) t) - \nabla_Y(\alpha(X) t) - \alpha([X,Y])t$

$=\nabla_X \nabla_Y s - \nabla_Y \nabla_X s- \nabla_{[X,Y]}s.$

share|improve this answer
    
Your assumption that $\nabla s = \alpha \otimes t$ appears to be unjustified. There's no reason to believe that $\nabla s$ is ever a pure tensor except in trivial cases. –  Zhen Lin Jan 26 '12 at 21:03
    
The first step is slightly problematic. How did you conclude that $\nabla s = a\otimes t$? Given $V, W$ vector spaces, it is not true that every element of $V\otimes W$ can be written as $v\otimes w$ where $v\in V$ and $w\in W$. (The elements $v\otimes w$ are only the rank-1 elements...) –  Willie Wong Jan 26 '12 at 21:04
    
Here is how I thought (in fact, this assumption appears in D. Huybrechts book) . The derivative $\nabla s$ is a sum of terms of the form $\alpha_i \otimes t_i$. From my computation we get $F(X,Y)(s) = \nabla (\sum \alpha_i \otimes t_i) = \sum \nabla (\alpha_i \otimes t_i) = \sum \nabla_X (\alpha_i(Y) t_i) - \nabla_Y(\alpha_i(X) t_i) - \alpha_i([X,Y])t_i = \nabla_X \nabla_Y s - \nabla_Y \nabla_X s- \nabla_{[X,Y]}s$. Where is my mistake? –  Lucas Kaufmann Jan 26 '12 at 21:28

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.